Strengthening the Law on Wildlife Conservation: The Malaysian Experience - Mustafa, Maizatun; abu hanifah, norha; kamaruddin, hanim; loh, ing hoe; hashim, normawati; Ibrahim, Irini (2017)
The period of 1970s was the time when Malaysia started to experience environmental problems including various threats facing the wildlife as a result of rapid economic growth, deforestation and urbanization. In an effort to solve these environmental problems, Malaysia took a number of countermeasures including the enactment of the Protection of Wildlife Act 1972. Over the years, it was apparent that while the Act was meant to safeguard endangered species and wildlife habitats, it weak penalties, limited scope of enforcement, and low risk of prosecution created an insufficient deterrent over various wildlife crimes including hunting and poaching. Subsequently, continuous threats to wildlife and fulfilment of international obligation have managed to persuade Malaysia to re-evaluate the efficacy of its wildlife conservation law including to amend the outdated penalties and widen the law’s scope of enforcement. Finally, after 38 years, the Protection of Wildlife Act 1972 was revoked, and a brand new legislation was passed, known as the Wildlife Conservation Act 2010. The new Act is aimed to improve and strengthen Malaysia’s wildlife legislation and is considered to be one of the most important statutes on wildlife conservation for Malaysia. This paper makes a comparison between the revoked 1972’s Act with the present Act for the purpose of highlighting improvement made within the new law in terms of its scope of enforcement, and new types of offences, and punishment it provides. Analysis of the provisions of the mentioned Acts shows that the current law expands the extent of enforcement and penalties. With these expansion, the law can now be enforced on wider scope and range of actions or activities considered to be offences pertaining to wildlife. The conclusion that can be made from this paper is that such expansion which improve the legal situation of animals has greatly increased Malaysia’s ability to protect its wildlife and endangered species.